Sequential pathology after initial freshwater bath treatment for amoebic gill disease in cultured Atlantic salmon, Salmo salar L - Adams, MB; Nowak, BF (Journal of Fish Diseases, 2004)
Freshwater bathing is essential for control of amoebic gill disease (AGD) during the marine phase of the Tasmanian Atlantic salmon production cycle, a practice that is costly, production limiting and increasing in frequency. Although the pathogenesis of gill infection with Neoparamoeba sp. in nave Atlantic salmon, Salmo salar, is now understood, the progression of re-infection (post-treatment) required elucidation. Here, we describe the weekly histopathological progression of AGD from first to second freshwater bath. Halocline cessation and increased water temperature appeared to drive the rapid onset of initial infection prior to bathing. Freshwater bathing cleared lesions of attached trophozoites and associated cellular debris. Subsequent gill re-infection with Neoparamoeba. sp. was evident at 2 weeks post-bath and had significantly increased (P < 0.001), in severity by 4 weeks post-bath. No significant difference in gross pathology was observed until 4 weeks post-bath (P < 0.05). The re-infective progression of AGD was characterized by localized host tissue responses juxtaposed to adhered trophozoites (epithelial oedema, hypertrophy and hyperplasia), non-specific inflammatory cell infiltration (macrophages, neutrophils and eosinophilic granule cells) and finally advanced hyperplasia with epithelial fortification. During the post-bath period, non-AGD lesions including haemorrhage, necrosis and regenerative hyperplasia were occasionally observed, although no evidence of secondary colonization of these lesions by Neoparamoeba sp. was noted. We conclude that pathogenesis during the inter-bath period was identical to initial infection although the source of re-infection remains to be established.